PENGARUH PENGGUNAAN MEDIA FILM ANIMASI KARTUN TERHADAP KEMAMPUAN MENYIMAK MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD NEGERI 2 TANJUNG KERANG - Zalika Popiyanti; Bukman Lian; Hetilaniar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT This study aims to determine whether there is an influence of animated cartoon film media on the ability to listen to Indonesian language subjects in class IV students at SD Negeri 2 Tanjung Kerang. The research method used in this research is an experimental method with the form of Pre-Experimental Designs and using the One Group Pretest-Posttest Design. The research sample was 22 students of class IV A. The instruments in this study were pre-test and post-test. The data analysis technique in this study was to analyze the data by means of a paired sample t-test using IBM SPSS Statistics version 26. The results of this study indicated that the posttest average value was greater than the pretest average value (81.50 > 63.27 ). Then the value is greater than (14.029 > 2.080), with a sig (2 t-tailed) value less than 0.05 of 0.000 <0.05 with the results of the hypothesis = rejected and = accepted. So it can be concluded that this study shows that the use of animated cartoon film media has an effect on the ability to listen to Indonesian language subjects in class IV SD Negeri 2 Tanjung Kerang.